The Effect of Agreed Export Tonnage Scheme (AETS) Policy on Indonesia's Natural Rubber Exports to Japan - Safira Retna Hanivia; Suprehatin (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
Natural rubber is one of Indonesia's major agricultural export commodities. However, the export performance of Indonesia’s natural rubber to several destination countries experienced a downward trend during the 2011-2019 period. Japan is one of the leading export destinations for Indonesia’s natural rubber, experiencing a downward trend in export value. This study aims to analyze Indonesia’s natural rubber exports to Japan and its agreed export tonnage scheme (AETS) policy. The study utilized a monthly time series data from 2011 to 2019. The data were analyzed using descriptive qualitative and error correction model (ECM) methods. The results showed the implementation of AETS policy and world natural rubber price had significant effect on the export value of Indonesia’s natural rubber to Japan in the long-run, but it is not applied in the short-run. Indonesia needs to improve the quality and productivity of natural rubber production to increase the performance of Indonesia’s natural rubber exports to Japan. Furthermore, Indonesia needs to evaluate the effectiveness of the AETS policy on natural rubber.